La pudricion negra de la yuca (Manihot esculenta) causada por Scytalidium sp - Bejarano, C.A.; Laberry, R.; Orrego, A.; Lozano, J.C. (1991)
The symptoms caused in cassava by Scytalidium sp. and Diplodia manihotis are described and compared. NE Brazil and the northern coast and Valle del Cauca of Colombia are zones with appropriate ecological characteristics for an optimum disease development. Scytalidium sp. affected both roots and stems and therefore it is recommended to use healthy cuttings for planting as well as quarantine measures to avoid its introduction in noncontaminated zones but with conditions appropriate for its development. Etiological, epidemiological, and control studies are currently being conducted with respect to this pathological problem of cassava. (CIAT)